Computation of the impedance of a vacuum electron diode with emission current delay; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 921 - Egorov I. S. Ivan Sergeevich (2019, 2019)
Title screen